2021
DOI: 10.1155/2021/2234457
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Method of Clinical Nursing under the Medical Internet of Things Technology

Abstract: Internet of things technology began to spread to all industries of our lives; the application of medical internet of things in many hospitals highlighted its advantages and brought a lot of convenience to patients and medical staff. With the continuous progress of China’s medical reform and the continuous improvement of patients’ requirements for medical service quality, this paper discusses the application of medical internet of things in clinical nursing in ward, and the basic information collection, infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Machine learning can help management handle commercial data to make judgments and decisions on key issues in operations, optimize logistics information systems, optimize services, save space, and control inventory [24,25]. In the logistics industry, the Internet of Things technology provides it with comprehensive information collection capabilities [26,27]. RFID, GPS, infrared induction, sensors, and other technologies are used to collect commercial information anytime and anywhere to form a full range of spatiotemporal monitoring data.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning can help management handle commercial data to make judgments and decisions on key issues in operations, optimize logistics information systems, optimize services, save space, and control inventory [24,25]. In the logistics industry, the Internet of Things technology provides it with comprehensive information collection capabilities [26,27]. RFID, GPS, infrared induction, sensors, and other technologies are used to collect commercial information anytime and anywhere to form a full range of spatiotemporal monitoring data.…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.56294/saludcyt2023459 3 Homavazir Z, et al Nurse-engineer: new professional It has been suggested for about 25 years that nursing and engineering should have official education programs and links with other professionals. Both nurses and engineers employ science and technologies as well as creativity to find solutions to real-world issues, however, nurses place more emphasis on the skill of treatment and training of well-being improvement whereas engineers place that emphasis on the skill of layout & practicing of building.…”
Section: Nursingmentioning
confidence: 99%
“…In issues including healthcare information technology combination, patient security, and coordinating care, process modeling has aided in identifying targets for workflow modifications. (3) Engineers create and construct robotic and automated systems which can carry out rote and repeated nursing duties like patient monitoring, medication administration, and sample analysis. Automation decreases human error, improves accuracy, and releases nursing time for more difficult and crucial tasks.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%